Confluences of the Maullín River: local ways of life and biodiversity conservation (Revista LIDER, 2021)
The Maullín River is part of one of the main hydrographic basins in the Los Lagos region. From its origin in Lake Llanquihue to its mouth in the Pacific Ocean, this watercourse supports different riverside communities. Based on an ethnographic research, this article analyzes the different practices and ways of life historically deployed along the river, unraveling the relationships between humans and non-humans that are interwoven in its evolution. Likewise, the environmental problems that threaten its integrity and the different collective actions of defense and protection that lead to the creation of the Maullín River Wetlands Nature Sanctuary are identified.